Effect of Some Factors on Fertility and Milk Yield Traits of Simmental Cattle Raised in Teke Region of Türkiye - Öztürk, Y; Sari, M (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was conducted to determine the effects of some factors on the fertility and milk yield traits of Simmental breed cattle raised with different production scales in Teke Region. The research data includes 635 lactation records of Simmental cows raised in enterprises in Antalya, Burdur, Denizli and Isparta provinces between 2011 and 2017. Based on these data, the effects of factors such as enterprise scale, lactation number, season, calving year and province on fertility and milk yield were analyzed. It was determined that the farm scale, calving year and calving season had significant effects on the fertility traits of calving interval and service period (P<0.05). Also, it was determined that lactation number affected the number of inseminations per pregnancy (P<0.05). Province had significant effects on lactation length, 305-day milk yield, lactation milk yield and drying time (P<0.05). Enterprise scale had significant effects on 305-day milk yield and lactation milk yield (P<0.05). Calving year affected lactation length, lactation milk yield and drying time (P<0.05) (P<0.05). Results showed that there were significant relationships between farm scale, progeny and milk yield traits in Simmental breed cattle raised in the Teke Region, and as the farm scale increased, calving interval, service period, lactation milk yield and 305-day milk yield increased. Increasing enterprise scale allowed to increase herd management, care and feeding facilities with providing technological innovations. For this reason, it can be recommended that the developing and implementing comprehensive models on preventing breast, foot and nutritional diseases and economic efficiency should be applied to increase fertility and milk yield in dairy cattle farms.